Relations Among Teasing, Body Satisfaction, Self-Esteem, and Depression in Treatment-Seeking Obese African American Adolescents. (August 2013) - Porter, Jerlym S.; Stern, Marilyn; Mazzeo, Suzanne E.; Evans, Ronald K.; Laver, Joseph
The objective of this study was to examine correlates of weight-based teasing, self-esteem, and depression among 119 treatment-seeking obese African American adolescents aged 11 to 18 years. Body satisfaction was examined as a potential mediator of the association between teasing and self-esteem and teasing and depression. Study participants (mean age = 13.9 years; 72% female) completed measures evaluating teasing, self-esteem, depression, and body satisfaction. Body satisfaction was measured using a multiethnic figure rating scale and a measure of overall satisfaction with appearance. The results indicated an association between teasing and decreased self-esteem and increased depression. Males exhibited higher body satisfaction than females. Body satisfaction partially mediated the association between teasing and self-esteem and teasing and depression. These data suggest that body satisfaction is relevant to well-being among obese African American adolescents seeking weight loss treatment.